Kryptografia dynamiczna - Juzwiszyn, Jacek; Wilkowski, Andrzej (Dynamic cryptography, 2005)
The work refers utilizations of methods of the dynamic cryptography to the protection of the information. In the article given is the method ZT-UNITAKOD, making possible the creation of dynamic cryptosystems. Authors propose the also joint use from leaning methods on coding dynamic along with cryptosystems of the type RSA.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 356-360